A conceptual history of psychology : exploring the tangled web - Greenwood, John D. (Cambridge : Cambridge University Press, 2015)
In the new edition of this original and penetrating book, John D. Greenwood provides an in-depth analysis of the subtle conceptual continuities and discontinuities that inform the history of psychology from the speculations of the Ancient Greeks to contemporary cognitive psychology. He also demonstrates the fashion in which different conceptions of human and animal psychology and behavior have become associated and disassociated over the centuries. Moving easily among psychology, history of science, physiology, and philosophy, Greenwood provides a critically challenging account of the development of psychology as a science. He relates the remarkable stories of the intellectual pioneers of modern psychology, while exploring the social and political milieu in which they operated, and dispels many of the myths of the history of psychology, based upon the best historical scholarship of recent decades. This is an impressive overview that will appeal to scholars and graduate students of the history of psychology.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Psychology -- History